Pengaruh Model Problem Based Learning ( PBL) Berbantuan Media Flashcard Terhadap Hasil Belajar Siswa Pada Pelajaran Bahasa Indonesia di Kelas IV SDN 4 Sindue - Yumita M. Luok; Yusdin Bin Mahmudin Gagaramusu; Nurul Kamisani; Muhammad Aqil; Muhammad Fasli (JURNAL DIKDAS, 2025)
This study aims to examine the effect of the Problem Based Learning (PBL) model assisted by flashcard media on students’ learning outcomes in Indonesian language learning. The study employed a quantitative approach using a pre-experimental design with a one-group pretest–posttest model. The population and sample consisted of all fourth-grade students at SDN 4 Sindue in the 2024/2025 academic year, totaling 27 students. Data were collected through learning outcome tests and interviews. Descriptive and inferential statistical analyses were conducted using SPSS version 29. The results showed that the average pretest score was 49.70, while the posttest average score increased to 80.96. The paired sample t-test analysis indicated a significance value (Sig. 2-tailed) of 0.001, which is lower than 0.05. These findings demonstrate that the implementation of the Problem Based Learning model assisted by flashcard media has a significant effect on students’ learning outcomes in Indonesian language learning for fourth-grade students at SDN 4 Sindue.